Doprinos episkopa Atanasija (Jevtića) savremenoj liturgijskoj polemici u SPC - Vukašinović, Vladimir (Edinost in dialog, 2013)
Author of this paper by analyzing the four collections of liturgical texts and a translation - the reconstruction of the Liturgy of St. John Chrysostom from 14th century shows the basic principles of liturgical theology of the Bishop Athanasius Jevtic. He reveals the dynamic and creative and at the same time the traditional approach of mutual interaction and refraction of law of faith and law of prayer that characterize the theology of Bishop Jevtic.
Keywords: Jevtić, Atanasije; srbska pravoslavne cerkev; liturgika; polemike